탈장교정술의 방법에 따른 재발 유형의 차이 - 김동주(Dong-Ju Kim); 최한림(Han-Lim Choi); 선우영(Woo-Young Sun); 류동희(Dong-Hee Ryu); 장이찬(Lee-Chan Jang); 최재운(Jae-Woon Choi); 박진우(Jin-Woo Park) (Annals of surgical treatment and research, 2009)
Purpose: Recently, conventional tissue repairs are gradually being replaced by tension-free hernioplasties using meshes (mesh repairs) in hernia surgery. The aim of the present study was to evaluate patterns of recurrent hernias according to the types of previous hernioplasties. Methods: From August 2005 to July 2008, 18 hernioplasties were performed in recurrent cases at Chungbuk National University Hospital. All previous hernioplasties were performed at local hospitals except one case of ventral hernia. We reviewed the medical records and compared clinical features according to the types of previous hernioplasties. Results: Among the 18 recurrent hernias, there were 15 inguinal including 2 pediatric cases, an umbilical, and 2 incisional hernias. Among 13 adult inguinal recurrent cases, 5 occurred after tissue repair (3 indirect, 1 direct, and 1 pantaloon type) and 8 after mesh repairs (direct type in all). Recurrence developed earlier after mesh repairs than tissue repairs (median [min∼max]; 24 [0.1∼164] vs. 243 [60∼360] months, P=0.005). Other types of recurrence developed between 6 to 48 months after previous operations. Recurrent hernias after mesh repairs occurred preferentially along the margin of previous meshes. All cases were treated by mesh repairs except in pediatric cases. Median operation time and hospital stay for recurrent inguinal hernias were not different significantly by previous operations. Postoperative complications were minimal without recurrence during a median 5.5-(1.5∼25.5)-month follow-up. Conclusion: Recurrent hernias develop both after tissue repairs and mesh repairs. After mesh repairs, recurrences develop earlier and are more often associated with technical failure compared to tissue repairs. Purpose: Recently, conventional tissue repairs are gradually being replaced by tension-free hernioplasties using meshes (mesh repairs) in hernia surgery. The aim of the present study was to evaluate patterns of recurrent hernias according to the types of previous hernioplasties. Methods: From August 2005 to July 2008, 18 hernioplasties were performed in recurrent cases at Chungbuk National University Hospital. All previous hernioplasties were performed at local hospitals except one case of ventral hernia. We reviewed the medical records and compared clinical features according to the types of previous hernioplasties. Results: Among the 18 recurrent hernias, there were 15 inguinal including 2 pediatric cases, an umbilical, and 2 incisional hernias. Among 13 adult inguinal recurrent cases, 5 occurred after tissue repair (3 indirect, 1 direct, and 1 pantaloon type) and 8 after mesh repairs (direct type in all). Recurrence developed earlier after mesh repairs than tissue repairs (median [min∼max]; 24 [0.1∼164] vs. 243 [60∼360] months, P=0.005). Other types of recurrence developed between 6 to 48 months after previous operations. Recurrent hernias after mesh repairs occurred preferentially along the margin of previous meshes. All cases were treated by mesh repairs except in pediatric cases. Median operation time and hospital stay for recurrent inguinal hernias were not different significantly by previous operations. Postoperative complications were minimal without recurrence during a median 5.5-(1.5∼25.5)-month follow-up. Conclusion: Recurrent hernias develop both after tissue repairs and mesh repairs. After mesh repairs, recurrences develop earlier and are more often associated with technical failure compared to tissue repairs. KCI Citation Count: 0